PENERAPAN TEKNOLOGI DALAM PENGELOLAAN PILAH SAMPAH RUMAH TANGGA DI JALAN BUKIT CEMARA INDAH XI RT 06 RW 13 KELURAHAN METESEH KECAMATAN TEMBALANG - Buana, Lalu Yahya Surya; Praharseno, Fikri; Suwarto, Suwarto; Lestari, Nor Puji; Ariyanto, Arief Subakti; Mawardi, Mawardi; Suparman, Suparman; Wahjoedi, Wahjoedi; Parhadi, Parhadi; Devilito, Rio (Politeknik Negeri Semarang, 2024)
Waste is the remains of daily human activities and/or from natural processes in solid form, and the source of waste is the initial/first place where the waste is. Based on the chemical properties of waste it is grouped into two types, namely organic waste which consists of organic compounds (carbon, hydrogen, oxygen and nitrogen and are quickly decomposed/weathered) come from living/dead things. The second type is inorganic waste which consists of non-organic materials (difficult to be decomposed by soil microorganisms) so it is durable and does not decompose easily. This article contains a report on the implementation of community service regarding the application of technology in managing household waste sorting on Jalan Bukit Cemara Indah XI RT 06 RW 13 Meteseh Village, Tembalang District, Semarang City. The aim of this service is to provide guidance by means of mentoring and counseling in managing waste sorting in the community. The method used consists of three stages which include (1) the observation and needs analysis preparation stage, (2) the implementation of the service process, (3) the service finalization and evaluation stage. The result of this service is the implementation of assistance in waste sorting management which is supported by the construction of a waste sorting place for the community on Jalan Bukit Cemara Indah XI RT 06 RW 13, Meteseh Village, Tembalang District, Semarang City.